Human Rights for The Elderly Group in Indonesia: Elderly in The Era of Covid 19 - Anang Darwisyi Baidhowi (NEGREI: Academic Journal of Law and Governance, 2022)
The 1945 Constitution essentially guarantees that every citizen in national development in all aspects of life "promotes general welfare and social justice". Among the achievements of general welfare is the realization of better public health. The implication is that the life expectancy of the Indonesian population is increasing and the number of elderly or elderly people is increasing. However, the bad news regarding the Coronavirus Disease-19 (Covid-19) pandemic is that the elderly are vulnerable to being exposed to Covid-19. The data from the World Health Organization (WHO) shows that more than 95% of deaths occur at the age of 60 years or older (WHO, 2020). How is the elderly social protection provided by the government and society's elderly social institutions during the Covid-19 pandemi?, and what is the urgent need for these elderly social institutions in protecting the elderly during the Covid-19 pandemic? The methodology in this study uses a mixed method rapid study approach. Creswell interprets it as a research method characterized by the collection of quantitative data in the first stage, then followed by the collection and analysis of qualitative data in the second stage in order to support the results of the quantitative research conducted in the previous stage. The conclusion of this study states that the elderly have the right to obtain maximum protection. Ministry of Social Affairs R.I. as a government mandatory for the realization of the welfare of the elderly has an important and strategic role in this. For this reason, the Ministry of Social Affairs needs to continue to develop policies for the protection of the elderly according to contemporary dynamics. The study is an important instrument for developing policies, in this case the protection of the elderly. In this regard, the Center for Social Welfare Research and Development views the urgency of conducting a study on "Social Protection of the Elderly during the Covid-19 Pandemic in Government and Community Elderly Social Institutions" as an information and input for the development of the intended elderly protection policy.